Melt Rheology of High-Density Polyethylene (HDPE) and Polypropylene (PP) using Single-Screw Extruder - Alzarzouri, Fadi; Skočilas, Jan (Manufacturing Technology Journal, 2023)
Melt rheological properties of HDPE and PP were studied using single-screw extruder equipped by capillary rheometer head. The rheological experiments were carried out at 210°C, 220°C, and 230°C. The screw rota-tional speed varied from 5 to 130 RPM. Power law index (n), consistency index (K), and flow activation ener-gy (E) were determined. The results showed that n values at 210°C, 220°C, and 230°C for HDPE were 0.72, 0.73 and 0.76 respectively, and for PP were 0.40, 0.44, and 0.45. The consistency index (K) values for HDPE and PP decreased with the increased in temperature and the flow activation energy of PP was greater than that of HDPE.
Keywords: Melt rheology; Extruder; Power law; HDPE; PP